Genetic diversity study in Napier grass collections and progeny plants - Jones, Chris; Muktar, Meki; Gari, Abel; Hanson, Jean; Negawo, Alemayehu T.; Domelevo Entfellner, Jean-Baka; Lee, Ki-won; Habte, Ermias (2023)
Genetic diversity study in Napier grass collections and progeny plants. The dataset contains genome-wide sequence tags, in FASTQ file format, generated from the genotyping of 258 Napier grass accessions on the DArTseq genotyping-by-sequencing platform. Of these, sequence tags representing 105 Napier grass accessions have been published previously (see doi.org:10.1038/s41598-019-43406-0). The remaining 153 accessions are Napier grass progeny plants raised from seeds of 13 mother plants from the ILRI collection.